Frequency of Hypomagnesemia in Hospitalized Diabetic Hypokalemic Patients - Haque, Wasim Md Mohosinul; Khan, AR; Nazimuddin, Khwaja; Musa, AKM; Ahmed, AKM Shaheen; Sarker, Rene Suzan Claude (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Recent studies suggest that there is strong relationship between serum magnesium and diabetes. Low serum magnesium is one of the risk factors of diabetes mellitus and its complications, at the same time diabetes is one of the common causes of hypomagnesemia. Hypokalemia is also quite common in diabetic patient. When hypokalemia coexists with hypomagnesemia, the chance of ‘complications of hypokalemia' increase significantly. In addition, the correction of hypokalemia becomes difficult. However, the exact frequency of hypomagnesemia in diabetic hypokalemic patient is not yet defined. Therefore, the objective of the current study was to find out the frequency of hypomagnesemia in hospitalized diabetic hypokalemic patient. Thirty consecutive diabetic patients with hypokalemia admitted under medical unit 1 BIRDEM were included in this study. There were 20 Female; and 10 male, mean age was 52.33±12.97 years, duration of diabetes was 1 - 20 years, mean serum potassium was 2.37± .36m mol/l, The mean ± SD of serum magnesium was 0.67 ±0.26 m mol/l. Hypomagnesemia was present in 19 patients (63.3%). Fifteen normokalemic diabetic patients were taken as control. Only one subject had Hypomagnesemia in control. Sample mean of serum magnesium has been found significantly lower than general population (P=.001) and control (P=.034) Key words: Hypokalemia, hypomagnesemia, diabetes, frequency DOI: 10.3329/jbcps.v26i1.4227 J Bangladesh Coll Phys Surg 2008; 26: 10-13